Biocontrol agents transform the stability and functional characteristics of the grape phyllosphere microenvironment - He, Tao; Yang, Meng; Du, Hongyan; Du, Ronghui; He, Yueqiu; Wang, Sheng; Deng, Weiping; Liu, Yixiang; He, Xiahong; Zhu, Youyong; Zhu, Shusheng; Du, Fei (Frontiers in Plant Science, 2024)
The spread of grape leaf diseases has a negative impact on the sustainable development of agriculture. Diseases induced by Uncinula necator significantly affect the quality of grapes. Bacillus biocontrol agents have been proven effective in disease management. However, limited research has been conducted on the impact of biocontrol agents on the assembly and potential functions of plant phyllosphere microbial communities. The biocontrol bacteria B. subtilis utilized in this study can significantly reduce the disease index of powdery mildew (p＜0.05); concurrently, it exhibits a lower disease index compared to traditional fungicides. A comprehensive analysis has revealed that biocontrol bacteria have no significant impact on the diversity of phyllosphere fungi and bacteria, while fungicides can significantly reduce bacterial diversity. Additionally, biocontrol agents can increase the complexity of fungal networks and enhance the degree of modularity and stability of the bacterial network. The results also showed that the biocontrol agents, which contained a high amount of B. subtilis, were able to effectively colonize the grapevine phyllosphere, creating a microenvironment that significantly inhibits pathogenic bacteria on grape leaves while enhancing leaf photosynthetic capacity. In conclusion, biocontrol agents significantly reduce the grape powdery mildew disease index, promote a microenvironment conducive to symbiotic microorganisms and beneficial bacteria, and enhance plant photosynthetic capacity. These findings provide a basis for promoting biocontrol agents and offer valuable insights into sustainable agriculture development.